Economics of the Integrated Fish-chicken farming system (Longyam) in Tasikmalaya, Indonesia - Amie Kusumawardhani; Hussein, Mohd. Ariff; Chiew, Eddie Fook Chong (Asian Fisheries Society, 1994)
One of the ways to increase income among fish farmers in Tasikmalaya District in the southern part of Java Island in Indonesia is the adoption pf an integrated fish-chicken farming system known locally as longyam. The management of longyam is generally based on tradition, past experience and comparison with neighbors. The study examines the efficiency of the present management system and compares it with an optimal system generated by linear programming. The optimal solutions can substantially increase total net revenue. To achieve this, extension efforts should be intensified to introduce new technology, and managerial practices improved to increase productivity. Although increased income can also be achieved by expanding the land area, this alternative is not possible due to serious limitations of land availability.